Comparison of absorbable and permanent sutures for laparoscopic sacrocervicopexy: A randomized controlled trial. (15th October 2020) - Tagliaferri, Valeria; Ruggieri, Stefania; Taccaliti, Chiara; Gentile, Cosimo; Didonna, Teodora; D'asta, Marco; Legge, Francesco; Guida, Piero; Scambia, Giovanni; Guido, Maurizio
Abstract: Introduction: Pelvic organ prolapse is a common cause of morbidity and decreased quality of life among women and is treatable by laparoscopic sacrocolpopexy. Recent data suggest that absorbable sutures are a feasible and appealing option for mesh attachment given a potential decreased risk of complications related to mesh erosion. The aim of the present study was to demonstrate the non‐inferiority of absorbable sutures to permanent sutures for laparoscopic sacrocervicopexy. Material and methods: We performed a randomized, single‐blinded, non‐inferiority trial comparing late‐absorbable sutures (group A) to non‐absorbable sutures (group B) for anterior and posterior vaginal mesh fixation during laparoscopic sacrocervicopexy at a single center in Italy. The primary outcome was prolapse correction at 12 months after surgery, defined as the absence of a pelvic organ prolapse leading edge reaching or extending below the level of the hymen and the absence of bulge symptoms. Secondary outcomes included intraoperative parameters, postoperative characteristics, and long‐term morbidity. Statistical analyses were performed using STATA version 16. Results: A total of 150 patients with pelvic organ prolapse were prospectively randomized 1:1 into two groups (A or B). Baseline characteristics and intraoperative parameters including blood loss, operation time, and intraoperative complications were comparable between groups. The success rate was 100% in both groups and no differences in prolapse correction were observed. The rates of de novo urinary incontinence and persistent urinary incontinence were also similar between groups. The rate of mesh erosion at 12 months was 0% in group A and 4% in group B ( P = .24). Conclusions: Late absorbable sutures are non‐inferior to non‐absorbable sutures for laparoscopic sacrocervicopexy in terms of procedural success. Moreover we did not see any differences in terms of operative parameters, or intraoperative and postoperative characteristics, although the study was not powered to these outcomes.